X-ray computed microtomography of internal damage in fiber reinforced polymer matrix composites - Schilling, Paul J.; Karedla, BhanuPrakash R.; Tatiparthi, Arun K.; Verges, Melody A.; Herrington, Paul D. (Composites science and technology, 2005)
The recent appearance of several commercial systems makes X-ray microtomography (micro-CT) more accessible for laboratory testing. The current study was undertaken to assess the capabilities and limitations of micro-CT for the characterization of damage and internal flaws, including delamination and microcracking, in fiber-reinforced polymer–matrix composite materials. Samples with a variety of damage types and geometries, and of various dimensions, were investigated to assess the effect of the system resolution on the ability to determine the internal geometry of flaws. Particular attention is paid to the detection of microcracking, a subject of critical interest in the study of fiber-reinforced polymer–matrix composite laminates. The results demonstrate that X-ray microtomography can facilitate characterization of the internal geometry of flaws, including delamination, matrix cracking, and microcracking, in fiber-reinforced polymer laminates.